KORELASI KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR SISWA DI KELAS V SEKOLAH DASAR - Muharlina Wati; Siti Halidjah; Dyoty Aulya Vilda Ghasya (Universitas Tanjungpura, 2020)
Abstract The purpose of this article was to describe correlation between learning independence and student learning outcomes in thematic learning of grade V SDN 39 Pontianak City. Method used is a descriptive method with a form of correlation study research. Population in this study is all students of grade V SDN 39 Pontianak City. Sampling using purposive sampling technique with a sample number of 33 people of grade VB SDN 39 Pontianak City. Data collection techniques are indirect communication techniques and documentary study techniques. Communication techniques are not directly used to collect data on the independence of learning results with tools in the form of questionnaires while documentary study techniques are used to collect data on students' learning outcomes. Analysis of data conducted with statistical analysis showed that student learning independence averaged 78.9, student learning outcomes averaged 91.55, and correlation between student self-reliance and student learning outcomes of rhitung=0.118 with rtabel=0.344 sign age 5%. Based on the data, it is concluded that there is no correlation between learning independence and student learning results in thematic learning class V sdn 39 pontianak kota. Keywords: Correlation, Learning Independence, Learning Outcomes.